The Improvement of Articulation Ability on Bilabial Letters Using Abata Method in the Hearing Impaired Students - Mukhlisin, Mukhlisin; Aprilia, Imas Diana (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
This research aims to find out the effect of Abata method implementation in improving the articulation ability on bilabial letters in the hearing impaired child of Abata Boarding School. In the beginning of assessment, it was found that the child performed the phoneme substitution on all bilabial letters (p-b-m-w), in which all bilabial letters were pronounced like the letter 'w' that was imperfect. This research used SSR (Single Subject Research) method and A-B-A (Applied Behaviour Analysis) design. The subject in this research was a hearing impaired child in class II of Abata Boarding School in Temanggung. The data collection technique was implemented using a test of articulation ability on bilabial letters and observation. The data analysis used in this research was descriptive statistics, through direct observation on graphic and table. Based on the data processing, the mean level percentages were 25% in the baseline-1 phase, 60% in the intervention phase, and 72.5% in the baseline-2 phase. Calculation of the overlapping percentage from baseline-1 phase to intervention phase was 0%. The research shows the result that the Abata method is capable of improving the articulation capability on bilabial letters in the hearing impaired child of Abata Boarding School.